Self-efficacy and COVID-19 prevention behaviour among adolescents: A cross-sectional study - Kurnia, Anggraini Dwi; Rohmaniah, Evita; Masruroh, Nur Lailatul; Melizza, Nur; Bekti Prasetyo, Yoyok; Arindari, Dewi Rury (Gaceta Médica de Caracas, 2022)
Introduction: COVID-19 has become a serious epidemic in Indonesia, even in the corners of the earth. Every day COVID-19 patients continue to increase, and almost all circles of society are exposed to the virus regardless of age and gender. In dealing with conditions such as the current pandemic, it is necessary to have self-efficacy in good adolescent prevention practices. The purpose of this study was to determine the relationship between self-efficacy and the practice of preventing COVID-19 in adolescents.